HUBUNGAN SELF EFFICACY TERHADAP KEPATUHAN MINUM OBAT ANTI HIPERTENSI PASIEN RAWAT JALAN DI RSUD PRINGSEWU - Alfa Fahmi Almunawwar; Mida Pratiwi; Riza Dwiningrum; Wisnetty (PT. Hasba Edukasi Mandiri, 2025)
A low level of self-efficacy can hinder motivation, decision-making, and goal achievement. Therefore, it is important to know and understand the level of self-efficacy as a foundation in the efforts to improve personal quality and individual independence. The global prevalence of hypertension is 22% of the total population in the world. The purpose of the study is to determine the relationship between self-efficacy and adherence to antihypertensive medication in outpatient patients at Pringsewu Regional General Hospital. The design used in this study is a quantitative research type with a cross-sectional research design. The population in this study amounted to 245 respondents and a sample of 152 people using a purposive sampling technique. Data were analyzed using the chi square test, the time of the study was conducted on May 7-27, 2025 at Pringsewu Hospital. The results of the univariate analysis on the age frequency distribution showed that the majority were >35 years old, totaling 144 respondents (94.7%), with male respondents numbering 79 (52%), education level from elementary to junior high school totaling 79 respondents (52%), low self-efficacy among 90 respondents (59.2%), and low medication adherence among 84 respondents (55.3%). The results of the bivariate analysis using chi-square showed a p-value of (0.000 < 0.05). The conclusion is that there is a relationship between self-efficacy and adherence to antihypertensive medication among outpatient patients at RSUD Pringsewu. It is recommended that hypertension patients regularly visit healthcare services for blood pressure monitoring and to consistently take their medication.